2021
DOI: 10.1111/cns.13742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginkgolide in Ischemic Stroke patients with large Artery Atherosclerosis: Results from a randomized trial

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The reduction in PAF and its pathway were reportedly helpful to reduce the volume of infarction in acute phase ( Oberpichler et al, 1990 ). A recently clinical trial also confirmed that Ginkgolide helped in decreasing accumulation of PAF after ischemic stroke, which might be one of the mechanisms in reducing stroke recurrence ( Dong et al, 2021 ). Both Ginkgo biloba extract and its constituent ginkgolide were proved effectively attenuating the rtPA-induced disturbances in neurotransmitter, amino acid, energy, lipid, and nucleotide metabolisms ( Pietri et al, 1997 ; Huang et al, 2012 ; Li et al, 2013 ; Chen et al, 2018 ; Feng et al, 2019 ; Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The reduction in PAF and its pathway were reportedly helpful to reduce the volume of infarction in acute phase ( Oberpichler et al, 1990 ). A recently clinical trial also confirmed that Ginkgolide helped in decreasing accumulation of PAF after ischemic stroke, which might be one of the mechanisms in reducing stroke recurrence ( Dong et al, 2021 ). Both Ginkgo biloba extract and its constituent ginkgolide were proved effectively attenuating the rtPA-induced disturbances in neurotransmitter, amino acid, energy, lipid, and nucleotide metabolisms ( Pietri et al, 1997 ; Huang et al, 2012 ; Li et al, 2013 ; Chen et al, 2018 ; Feng et al, 2019 ; Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 88%
“…In this regard, intravenous thrombolysis with alteplase remains a viable treatment for the majority of AIS patients in many centers. A number of experimental studies showed the neuroprotective efficacy of Ginkgolide, which can inhibit the platelet aggregation and increase vascular recanalization in AIS patients ( Feng et al, 2019 ; Dong et al, 2021 ). Ginkgolide played a role as an inhabitation of PAF receptor, which was induced by ischemic stroke ( Joseph et al, 1989 ).…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in sex, age, or course of disease between the study groups, with comparable baselines. Most RCTs focused on GEDM (7 RCTs, 46.6%) ( Su et al, 2018 ; Feng et al, 2020 ; Sun et al, 2019 ; Zheng and Jiang, 2018 ; Huang et al, 2021 ; Bao and Peng, 2019 ; Wang et al, 2017 ), followed by GDI (4 RCTs, 26.6%) ( Dong et al, 2021 ; Zhang et al, 2021 ; Zhou, 2021 ; Liu, 2018 ), GBDP (1 RCT, 6.7%) ( Sun et al, 2018 ), HES (1 RCT, 6.7%) ( Qin et al, 2020 ), GSRI (1RCT, 6.7%) ( Liu et al, 2020 ), and HSYA (1 RCT, 6.7%) ( Hu et al, 2020 ). The course of treatment ranged from 7 days to 90 days.…”
Section: Resultsmentioning
confidence: 99%
“…GDI contains bilobalide and ginkgolides A, B, and C, which are commonly used in the clinical treatment of stroke in China to promote blood circulation and eliminate blood stasis. In one multi-center, randomized, double-blinded, placebo-controlled trial ( Dong et al, 2021 ) patients diagnosed with AIS with intracranial artery stenosis (ICAS) were assigned to either GDI or placebo treatment. The trial reported a favorable outcome with a greater proportion of mRS scores ≤2 on D28 and NIHSS score improvement (NIHSS baseline -NIHSS 28D ) in the GDI-treated group compared with the placebo group [RR mRS = 1.49, 95% CI (1.01, 2.20), p = 0.042; MD NIHSS improvement = 0.37, 95% CI (0.07, 0.68), p = 0.016].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation